2003
DOI: 10.1081/ese-120023336
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Mixed Pharmaceutical Industry and Domestic Wastewater by Sequencing Batch Reactor

Abstract: Raw mixed pharmaceutical industry and domestic wastewater characteristics are such as BOD5 = 90-130 mg L(-1), COD = 200-300 mg L(-1), SS = 900 mg L(-1), pH = 6.4-6.8, T = 20 degrees C, NH3 = 26 mg L(-1), PO4(3-) = 8.5 mg L(-1). In treatment plant, the parameters such as BOD5, NH3, PO4(3-), SS, MLVSS, pH, temperature, sludge volume and microorganisms predominance are studied, under constant sedimentation time (30 min) against variable aeration times. As a second step, the same parameters are studied under the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…SBR is an activated sludge method of treatment in which separate tanks for aeration and sedimentation are not required and there is no sludge return. This type of process is ideal for use in small systems or when land is limited (Ileri et al, 2003). In one study, removal rates of 82 % Biochemical oxygen demand (BOD), 88 % COD, 96 % NH 3 and 98 % Suspended solids (SS) from domestic and pharmaceutical wastewater were achieved with a SBR operated for a 4 h aeration and a 60 min sedimentation period (Ileri et al, 2003).…”
Section: Conventional Treatment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SBR is an activated sludge method of treatment in which separate tanks for aeration and sedimentation are not required and there is no sludge return. This type of process is ideal for use in small systems or when land is limited (Ileri et al, 2003). In one study, removal rates of 82 % Biochemical oxygen demand (BOD), 88 % COD, 96 % NH 3 and 98 % Suspended solids (SS) from domestic and pharmaceutical wastewater were achieved with a SBR operated for a 4 h aeration and a 60 min sedimentation period (Ileri et al, 2003).…”
Section: Conventional Treatment Methodsmentioning
confidence: 99%
“…This type of process is ideal for use in small systems or when land is limited (Ileri et al, 2003). In one study, removal rates of 82 % Biochemical oxygen demand (BOD), 88 % COD, 96 % NH 3 and 98 % Suspended solids (SS) from domestic and pharmaceutical wastewater were achieved with a SBR operated for a 4 h aeration and a 60 min sedimentation period (Ileri et al, 2003). In another study, slightly lower removal efficiencies at between 63-69 % of COD levels were achieved using SBR technology (Aguado et al, 2008).…”
Section: Conventional Treatment Methodsmentioning
confidence: 99%
“…However, effluent samples revealed considerably high toxicity even though the physicochemical parameters were not unusual (Table 1). The high toxicity was not reported in the other pharmaceutical industrial complexes, such as Taiwan, Turkey, and Malaysia (Ileri et al, 2003;Chang et al, 2008;Herumurti et al, 2008). All samples showed toxicity greater than 16 TU, which suggests that the present treatment methods of WWTP are not sufficient to remove the toxicants from the wastewater.…”
Section: General Parameters and Results Of Wetmentioning
confidence: 87%
“…To sum up, such a plant is environment friendly, minimize the use of chemicals, cost-effective and easy tooperate for industrial effluent treatment. Ileri et al (2003) Ng et al (1989) reported the biological treatment of pharmaceutical wastewater and achieved remarkable reduction in COD and BOD levels by using the sequencing batch reactor (SBR) concept. Altaf and Ali (2010) carried out studies on pharmaceutical wastewater treatment using sequential batchreactor (SBR) and developed a biological method for the analysis of relative toxicity operating with dissolved oxygen 2.0 mg/l, at different pH (6.62, 6.69, 6.79 and 6.9) for 7, 14 and 21 days treatment.…”
Section: Aerobic Treatmentmentioning
confidence: 99%
“…Raj and Anjaneyulu (2005) analysed pharmaceutical wastewater after chemical treatment and obtained the mean value of the following parameters with standard deviation (SD): pH 12.9 ± 0.28, EC 25,230 ± 158.1, total solids 20,030 ± 317.4 mg/l, TDS 16,190 ± 108.4 mg/l, TSS 3,720 ± 192.35 mg/l, COD 8,480 ± 414.73, BOD 4,800 ± 316.23 mg/l, phosphate nil mg/l, nitrates 1,400 ± 306.2, alkalinity 1,100 ± 128.6 mg/l, sulphates 4,900 ± 207.5 mg/l and chlorides 950 ± 64.1 mg/l. Ileri et al (2003) characterized the raw mixed pharmaceutical industrial wastewater as BOD = 90-130 mg/l, COD = 200-300 mg/l, suspended solids = 900 mg/l, pH = 6.4-6.8, temperature = 20°C, ammonia = 26 mg/ l, phosphate = 8.5 mg/l. Lapara et al 2001 achieved 7,320 ± 160 mg/l COD value in PIWW prior to treatment.…”
Section: Characteristics Of Pharmaceutical Industries' Wastewatermentioning
confidence: 99%